Attitude Formation Through Exploration Valence Asymmetries. [article]. - Fazio, Russell H.
The formation of attitudes toward novel objects was examined as a function of exploratory behavior. An initial experiment, in which participan ts played a computer game that required them to which stimuli, when sampled, produced favorable or unfavorable outcomes, demonstrated learning, attitude formation, and generalization to novel objects. The findings also revealed 2 intersting valence asymmetries : a learning asymmetry involving better learning for negatively valenced than positively valenced objects and an generalization asymmetry involving stronger generalization as a function of negative than of positive attitudes. Findings from 4 experiments led to an explanation of the learning asymmetry in terms of infomation gain being contingent on approac behavior and related the generalization asymmetry to a negativity bias that weighs resemblance to a known negative more heavily than resemblance to a positive.-- (from the author).